Pengaruh Kualitas Produk Dan Harga Terhadap Kepuasan Pengguna Kartu Telkomsel Yang Dimoderasi Oleh Brand Image Pada CV. Sinar Telekom - Pulungan, Tio Candra; B., Mesra (Jurnal Manajemen Akuntansi (JUMSI), 2025)
This study aims to determine the effect of product quality and price on the satisfaction of Telkomsel card users moderated by brand image at CV Sinar Telekom. This type of research is quantitative. The population in this study were consumers who purchased Telkomsel cards at CV Sinar Telekom. With the Accidental Sampling sampling technique using the lemeshow formula, a sample of 100 respondents was obtained. The data analysis technique used in this study is the Data analysis technique in this study uses descriptive statistical analysis and Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of this study indicate that product quality does not affect consumer satisfaction. However, price affects consumer satisfaction. In addition, brand image can strengthen the influence of product quality and price on consumer satisfaction of Telkomsel cards at CV Sinar Telekom.